2011
DOI: 10.1007/s10236-011-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation mechanisms for mesoscale eddies in the Gulf of Lions: radar observation and modeling

Abstract: Coastal mesoscale eddies were evidenced during a high-frequency radar campaign in the Gulf of Lions (GoL), northwestern Mediterranean Sea, from June 2005 to January 2007. These anticyclonic eddies are characterized by repeated and intermittent occurrences as well as variable lifetime. This paper aims at studying the link between these new surface observations with similar structures suggested at depth by traditional acoustic Doppler current profiler measurements and investigates the eddy generation and driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 79 publications
2
41
0
Order By: Relevance
“…A growing number of European studies have been developed on the use of HFR data toward a better understanding of the surface ocean coastal dynamics (Shrira et al, 2001;Rubio et al, 2011;Schaeffer et al, 2011;Uttieri et al, 2011;Sentchev et al, 2013;Berta et al, 2014a;Shrira and Forget, 2015;Stanev et al, 2015;Falco et al, 2016). Moreover, since HFR data provide measurements of currents with a relatively wide spatial coverage and high spatial and temporal resolution in near real time (there are systems with lags of just 20 min, after generating the data), they have become invaluable tools in the field of operational oceanography.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of European studies have been developed on the use of HFR data toward a better understanding of the surface ocean coastal dynamics (Shrira et al, 2001;Rubio et al, 2011;Schaeffer et al, 2011;Uttieri et al, 2011;Sentchev et al, 2013;Berta et al, 2014a;Shrira and Forget, 2015;Stanev et al, 2015;Falco et al, 2016). Moreover, since HFR data provide measurements of currents with a relatively wide spatial coverage and high spatial and temporal resolution in near real time (there are systems with lags of just 20 min, after generating the data), they have become invaluable tools in the field of operational oceanography.…”
Section: Introductionmentioning
confidence: 99%
“…The ocean coastal dynamics of the northwestern Mediterranean (NWM) Sea has been studied over the last decades using observations (e.g., Millot, 1999;Petrenko, 2003;Sammari et al, 1995;Allou et al, 2010), modeling (Echevin et al, 2003;Casella et al, 2011;Ourmières et al, 2011;Pairaud et al, 2011), or a combination of both (Schaeffer et al, 2011b;Guihou et al, 2013). The NWM is a micro-tidal sea (e.g., Alberola et al, 1995) and its dynamic is mainly governed by wind forcing and by the Northern Current (NC), which is the northern branch of the general circulation of the NWM Sea (Millot, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As the time progresses during the wind events E1 and E3, the zonal geostrophic velocity weakens and as a consequence the angle is expected to decrease, as shown in suggested by the current reversals in Fig.4, that could be due for instance to the interaction with the outflow from the Gulf of Lyon (Schaeffer et al, 2011). Ocean Sci.…”
Section: Discussionmentioning
confidence: 99%
“…CTD data were processed with dedicated Matlab routines taking care of all classic CTD response times and alignment issues, and all parameters were rebinned onto a regular vertical grid with a step of 2 dbar. Due to the use of an unpumped CTD and to the variable speed of the autonomous vehicle, the corrections were made speed-dependent using the glider speed computed through pressure variations 20 and tilt angle. The thermal lag of the conductivity sensor was dealt also with speed-dependent coefficients (Morison et al, 1994) experimentally found through the technique proposed by Garau et al (2011).…”
mentioning
confidence: 99%